Lentes de gênero sobre o Sindicato dos Trabalhadores em Educação Básica da Rede Oficial do Estado de Sergipe (SINTESE) - Dantas, Adenilde de Souza (2017)
The present research aims to analyze and give visibility to gender relations, to the construction of identities of the Union of Workers in Basic Education of the Public School System in the State of Sergipe (SINTESE) in the Northeast of Brazil, highlighting advances in the democratization of social workforce relations. Due to the nature of the object, a qualitative approach of historical-dialectic inspiration has been adopted, giving emphasis to the dimensions of macro-micro, collective-individual, objective-subjective conflicts and contradictions. The case study was chosen as methodology by consulting different sources of information: review of the related literature; documents of the thesis bank of Capes and of Thesis of SINTESE Congresses from years 2006, 2012 and 2015; questionnaires to characterize the profile of leaders of union; semi-structured interviews carried out with six leaders of the Executive Direction of SINTESE, working in the sub-regional offices of the entity, and with Members of the Council of Representatives of the SINTESE/CERES; and direct observation of activities developed in the institution to capture the relations of power among the militants, and the binarism of man/woman was observed, as well as the social relations among women themselves, women and men. Results of this research show the predominance of men in the union academic staff, in executive positions of power/decision-making, particularly in the North, Southwest and Center-West regions. In the Southern region, women are majority when compared to men. In the Northeast, the number of men and women taking over directions in the unions is well balanced. In Sergipe state, SINTESE presents a major participation of women in relevant management positions. Nevertheless, this fact does not mean the incorporation of gender discussion by the union. This is because the culture of a single agenda in the organization is predominantly focused on class issues, thus, it does not favor the gender focus, and it still shows aspects of existing male domination in the trade union space.